Developing A Strategic Plan for Strengthening Organizational Resilience Through Employee Empowerment and Engagement in KMSS-Mandalay - Ning, Khui Shing; Tantasanee, Somchai (ABAC ODI JOURNAL Vision. Action. Outcome, 2023)
Since the Military Coup, in 2021, several organizations in Myanmar have been dealing with a political crisis that has led to financial limits and donor agency withdrawal. This situation has also significantly influenced the loss of work opportunities, physical insecurity and facing challenges for organizational survival. This research has four main objectives:1) To explore how employees define " Organizational resilience and Employee empowerment and Engagement” during the political crisis in Myanmar, 2) To discover the strengths of Employee empowerment, engagement, and organizational resilience in KMSS-Mandalay, 3) To determine the shared aspirations given results and opportunities of employee’s empowerment and engagement towards organizational resilience, and 4) To develop a strategic plan for strengthening organizational resilience through employee empowerment and engagement in KMSS-Mandalay based on the findings. The research questions for this study, which focuses on resilience during times of crisis in Myanmar, were mostly constructed by applying the Appreciative Inquiry (AI) Model. Regardless of gender or marital status, ten workers from various level positions were horizontally chosen to participate in the research following the objectives of the study. Phenomenology was used to gain insight into team members’ lived experiences through structured interviews. The researchers asked two coders from fellowships who were well-versed in the topic selection by content analysis. The results demonstrate that strengths and dreams are essential components of resilient organizations. Resilience, employee empowerment, and engagement powered by AI are all elements of strengths. The goals include sustaining the preferred aspirations both now and beyond the crisis, employee contributions to the organization’s future, and organizational success and sustainability opportunities. Finally, a strategic plan is developed based on employee strengths and dreams for the future to improve organizational resilience.